EVALUATION OF EFFICIENCY AND SAFETY OF THROMBOPROPHYLAXIS AFTER ORTHOPEDIC OPERATIONS - A. V. Vybivantseva (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Prevention of deep vein thrombosis and pulmonary artery thromboembolism using heparin is a gold standard in orthopedics. The aims of the work were to evaluate and to compare efficiency and. safety of thromboprophylaxis in orthopedics using Pradaxa and Clexane in long-term follow-up. 96 patients are included in research. Follow-up information on all patients was collected either through telephone contact with the patients or by questionnaire. Conclusions: The number of respondents appeared insufficient for the actual check of an initial hypothesis. In modeling outcomes plausibility of a hypothesis isn't disproved. Recommendations about VTE prevention after discharge in our study are differed from the accepted standards.